Complex Post-Traumatic Stress in People with Different Types of Child-Mother Attachment - Tatyana V. Kapustina; Ekaterina A. Rodnikova (СибСкрипт, 2023)
Violence affects mental development and health. Childhood traumas trigger a range of different symptoms, which may manifest as a complex post-traumatic stress disorder (CPTSD). This empirical study focused on the correlation between CPTSD and the type of child-mother attachment. The experiment involved 82 people aged 32–60 y.o., 30 of which were diagnosed with CPTSD while 52 people served as control. Psychological profiling showed that the CPTSD group demonstrated ambivalent and disorganized types of child-mother attachment. However, the Fisher’s ratio test revealed no significant differences for the ambivalent type. Probably, in this case, the negative childhood experience was not traumatic enough to lead to CPTSD. The predominant disorganized type of child-mother attachment formed target points for providing psychological assistance to people with CPTS.